KAJIAN MANFAAT PEMBANGUNAN JALAN LINGKAR KOTA LHOKSEUMAWE (STUDI KASUS JALAN LINGKAR KOTA LHOKSEUMAWE) - Rijalul Qadri; Muhammad Isya; Sofyan M. Saleh (JURNAL TEKNIK SIPIL, 2017)
Abstract: The city of Lhokseumawe is the administrative city of the central government and all economic, political, social and cultural activities. Along with the existence of the existing road that is the road of freedom of the west with a road length of 5 km wide road of 7 m average consisting of 2 lane 2 direction (2/2 UD) causing congestion, traffic accidents and increasing travel time. To anticipate the problem in 2012 the government of Lhokseumawe City began to budget for the construction of Lhokseumawe City Ring Road starting from Simpang Loskala - Simpang Lestari with a total length of 7.6 km road, which has been built currently 3 km to Gampong Ujong Blang is still In the measurement and land acquisition stage. The average road width of 14 m consists of 4 lane 2 lanes (4/2 D) is a new access road to Lhokseumawe City. The purpose of this study was to calculate VOC and time savings for existing and alternative road routes, to know respondent perceptions and to evaluate economic feasibility based on BCR, NPV and EIRR. The results of this study indicate that the average annual traffic volume (LHRT) on alternative roads is 4.279 vehicle/day in 2017; The difference in total time value obtained by IDR 189,877,-/ vehicle and VOC difference is IDR 3,289 / vehicle; And economic feasibility of Lhokseumawe Ring Road development is obtained in 2036. The EIRR value obtained is at the discount rate of 17.27%, it indicates that the development of Ring Road / alternative is very feasible to be implemented with bank loan interest rate up to 17.27%.Abstrak: Kota Lhokseumawe merupakan kota administratif pusat pemerintahan dan segala kegiatan ekonomi, politik, sosial dan budaya. Seiring padatnya jalan eksisting yaitu jalan merdeka barat dengan panjang jalan 5 km lebar badan jalan rata-rata 7 m yang terdiri dari 2 lajur 2 arah (2/2 UD) yang mengakibatkan kemacetan, kecelakaan lalulintas dan bertambahnya waktu tempuh. Untuk mengantisipasi permasalahan tersebut pada tahun 2012 pemerintah Kota Lhokseumawe mulai menganggarkan dana untuk Pembangunan Jalan Lingkar Kota Lhokseumawe yang dimulai dari Simpang Loskala – Simpang Lestari dengan total panjang jalan 7,6 km, yang telah dibangun saat ini 3 km sampai dengan Gampong Ujong Blang selanjutnya masih dalam tahapan pengukuran dan pembebasan lahan. Lebar badan jalan rata-rata 14 m yang terdiri dari 4 lajur 2 jalur (4/2 D) merupakan jalan akses baru menuju Kota Lhokseumawe. Tujuan Penelitian ini untuk menghitung BOK dan penghematan nilai waktu untuk rute jalan existing dan jalan alternatif, mengetahui persepsi responden serta mengevaluasi kelayakan ekonomi berdasarkan BCR, NPV dan EIRR. Hasil penelitian ini menunjukkan bahwa Volume lalu lintas harian rata-rata tahunan (LHRT) pada jalan alternatif didapat 4.279 kend/hari pada tahun 2017; Selisih nilai waktu total yang diperoleh sebesar Rp 189.877,-/kendaraan dan selisih BOK adalah Rp 3.289,- /kendaraan; dan Kelayakan ekonomi pembangunan jalan Lingkar Kota Lhokseumawe didapat pada tahun 2036. Nilai EIRR yang diperoleh yaitu pada discount rate 17,27%, ini menunjukkan bahwa pembangunan jalan lingkar/alternatif sangat layak untuk dilaksanakan dengan suku bunga pinjaman bank sampai dengan 17,27%.